#11F, more women in sciences (REVISTA SAYWA, 2023)
Recognizing the role of women and girls in science, not only as beneficiaries but also as agents of change, will help accelerate progress towards achieving the sustainable development goals. In this section, we will learn the opinion of María Isabel Olarte, who was a participant and representative of Colombia in OLAA2018, OLAA2020, OLAA2021, IOAA2018, IOAA2019, GeCAA2020, IOAA2021.